Analysing and interpreting the yield curve - Choudhry, Moorad (Singapore : Wiley, 2004)
One of today's fastest growing investment and risk management mechanisms such as synthetic securitisations and structured products are revolutionizing the financial industry and changing the way banks, institutional investors, and securities traders do business both domestically and globally. While potentially beneficial, these important instruments are complex structures that are often misunderstood and frequently mishandled. This groundbreaking book offers a succinct and focused resource complete with global case studies on how they work, and how best to capitalize on them.
oif 02/09/15
Loan
Keywords: Bonds -- Valuation -- Econometric models